Low temperature nucleation of thermochromic VO2 crystal domains in nanocolumnar porous thin films. (18th June 2023) - Alcaide, A M; Regodon, G; Ferrer, F J; Rico, V; Alvarez, R; Rojas, T C; González-Elipe, A R; Palmero, A
Abstract: The low temperature formation of monoclinic VO2 crystal domains in nanocolumnar vanadium/oxygen thin films prepared by magnetron sputtering at oblique angles is analyzed. The synthesis procedure involved the deposition of amorphous nanocolumnar VO1.9 thin films at room temperature and its subsequent annealing at temperatures between 250 °C and 330 °C in an oxygen atmosphere. The thermochromic transition of these films was found at a temperature of 47 °C when the annealing temperature was 270 °C and 58 °C when the annealing temperature was 280 °C and 290 °C, presenting a clear drop of the optical transmittance in the infrared region of the spectrum. The significant downshift in the temperature window to obtain VO2 in comparison with compact films and other strategies in literature is explained by the particular morphology of the nanocolumnar structures, which contains numerous defects along with open and embedded porosity.